Correlation between mutations in liaFSR of enterococcus faecium and MIC of daptomycin: revisiting daptomycin breakpoints (2012)
Mutations in liaFSR, a three-component regulatory system controlling cell-envelope stress response, were recently linked with the emergence of daptomycin (DAP) resistance in enterococci. Our previous work showed that a liaF mutation increased the DAP MIC of a vancomycin-resistant Enterococcus faecalis strain from 1 to 3 μg/ml (the DAP breakpoint is 4 μg/ml), suggesting that mutations in the liaFSR system could be a pivotal initial event in the development of DAP resistance. With the hypothesis that clinical enterococcal isolates with DAP MICs between 3 and 4 μg/ml might harbor mutations in liaFSR, we studied 38 Enterococcus faecium bloodstream isolates, of which 8 had DAP MICs between 3 and 4 μg/ml by Etest in Mueller-Hinton agar. Interestingly, 6 of these 8 isolates had predicted amino acid changes in the LiaFSR system. Moreover, we previously showed that among 6 DAP-resistant E. faecium isolates (MICs of >4 μg/ml), 5 had mutations in liaFSR. In contrast, none of 16 E. faecium isolates with a DAP MIC of ≤2 μg/ml harbored mutations in this system (P < 0.0001). All but one isolate with liaFSR changes exhibited DAP MICs of ≥16 μg/ml by Etest using brain heart infusion agar (BHIA), a medium that better supports enterococcal growth. Our findings provide a strong association between DAP MICs within the upper susceptibility range and mutations in the liaFSR system. Concomitant susceptibility testing on BHIA may be useful for identifying these E. faecium first-step mutants. Our results also suggest that the current DAP breakpoint for E. faecium may need to be reevaluated.